HUBUNGAN JARAK KELAHIRAN DAN SIKAP IBU DENGAN PENANGANAN SIBLING RIVALRY PADA ANAK USIA 3-5 TAHUN DI KELURAHAN SIRANDORUNG KAB.LABUHANBATU TAHUN 2020 - Septa Dwi Insani (JURNAL ILMIAH DHDT - KEBIDANAN, 2020)
The rivalry between siblings usually occurs at the age of the first five years when the older sister's position as the center of attention is replaced by her baby sister, enough time to educate her children, then it will be fair so all feel the same love. However, for those who do not understand how to educate a good child, it is very possible for a child who cries to be pinched and maybe even be whipped and other ways of physical abuse. year in Kel.Sirandorung Regency, Pelabuhanbatu in 2020. This study is a quantitative study with a cross sectional type of research that aims to find out how the close relations between the two variables. The results of the study with a population of 48 people, purposive sampling, statistical analysis using Chi-Square showed a significant relationship between birth spacing with Sibling Rivalry in Kel.Sirandorung 0.000 <0.05. There is a significant relationship between parents' attitudes with sibling rivalry in Kel. Sandandorung obtained results of 0,000 <0.05. The conclusion of this study is that the better the birth spacing and the attitude of mothers to eat will decrease the occurrence of sibling rivalry in children to be expected to health workers to be able to socialize about sibling rivalry especially to parents who have two or more children.